Pengelolaan MGMP Dalam Meningkatkan Profesionalisme Guru - Andri Suhendri (LPPM Politeknik Pratama, 2023)
This research has a background, namely that the MGMP IPA of Ciamis Regency conducts management in order to increase teacher professionalism. Good MGMP management is expected to increase teacher professionalism, especially in terms of knowledge, abilities, skills, attitude and teacher habits. This study aims to analyze and describe: 1) Management of the Ciamis Regency Science MGMP in increasing teacher professionalism; 2) Obstacles in managing the MGMP IPA of Ciamis Regency in increasing teacher professionalism; 3) Efforts to overcome obstacles to the management of the Ciamis Regency IPA MGMP in increasing teacher professionalism. The research method used is descriptive with a qualitative approach. Data collection techniques were carried out through interviews, observation and documentation studies. The informants of this study were science supervisors, school principals, chairmen, secretaries and members of the Ciamis IPA MGMP. Data analysis techniques are carried out through data reduction, data presentation, and drawing conclusions/verification. The results of the study show that: 1) MGMP management in terms of planning, organizing, directing and supervising has been carried out properly according to standards so as to increase teacher professionalism; 2) There are obstacles encountered in managing the MGMP to increase teacher professionalism; 3) There have been efforts made to overcome the obstacles encountered in managing the MGMP to increase teacher professionalism